Application of Microsoft Sway–Based Digital Learning Media on Environmental Change Material to Enhance Scientific Literacy Skills of Grade 10 Students of Sampoerna Academy Surabaya - Aruna Nur Setiawan; Herlina Fitrihidajati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2026)
The current curriculum requires students to possess skills to solve real-world problems through learning. Scientific literacy is defined as students’ ability to solve problems using reliable information from research. This study was conducted using an international curriculum, namely the Cambridge curriculum, which is implemented at Sampoerna Academy Surabaya and emphasizes the development of students’ scientific literacy skills. Therefore, this study aimed to describe the consistency of using Microsoft Sway–based learning media in achieving learning mastery, consistency in improving learning outcomes, and students’ responses to the use of Microsoft Sway–based learning media on environmental change material in relation to scientific literacy skills. The study employed a pre-experimental one-group pretest–posttest design. The research sample consisted of 20 tenth-grade students at Sampoerna Academy Surabaya International High School. The instruments used included test questions to measure learning mastery with a minimum mastery standard of 50% and improvement in scores, as well as a response questionnaire to assess students’ responses. The collected data were analyzed using descriptive quantitative methods with simple statistics, including averages and percentages. The results showed that all students achieved learning mastery, with an average post-test score of 92.19%. The N-Gain analysis indicated an average score of 0.77, categorized as high improvement. Questionnaire results showed positive student responses with an average of 95.71%. Based on these findings, it can be concluded that Microsoft Sway–based learning media consistently improve students’ scientific literacy skills in environmental change material.